Quality of Life of Children After Completion of Surgical Treatment for Anorectal Malformation: A Single-Centre Cross-Sectional Study in South- Western Uganda - Mucunguzi, Denis; Oyania, Felix; Egesa, Walufu Ivan; Aturinde, Mercy; Mutakooha, Marvin Mwesigwa; Kyengera, Kisitu Dan (Research square, 2023)
Background: Anorectal malformations (ARMs) range from minor abnormalities such as imperforate anus to complex forms such as cloaca, and are often associated with other anomalies and residual functional stooling problems. The present study aimed to evaluate the quality of life (QoL) of children after surgical treatment for ARMs at Mbarara Regional Referral Hospital (MRRH) in South-Western Uganda. Methods: In this cross-sectional study, we enrolled children who had completed surgical treatment for ARMs between 2014 to 2021 at MRRH. A 23-item PedsQL 4.0 inventory was used to evaluate health-related QoL in children using a multidimensional parent proxy reporting for children aged 3 months to 7 years and child self-reporting for children aged 8 to 17 years. Regression analysis was used to determine the association between sociodemographic and clinical variables and QoL. Crude and adjusted coefficients and their corresponding 95% confidence intervals (CI) were calculated. The significance level was set to a p-value < 0.05. Results: A total of 88 participants (F:M ratio = 1.15:1) aged 3 months to 18 years with a median age of 4.5 (IQR 3– 7) years were enrolled. The median age at diagnosis of ARM and preliminary diverting colostomy was 3 days (range: 2 to 30 days) and 3 days (range: 2 to 60 days) respectively. Rectovestibular fistulas, 47 (53.4%) were the most prevalent subtype of ARMs, and 5.7% of children had associated anomalies. Over one-third of the participants (38.6%) had definitive surgery after 3 years of age, and PSARP was the most common procedure. The average PedsQL score was 94 out of a maximum score of 100. The mean physical functioning score was 96.7 in males and 98.9 in females. The overall mean emotional functioning score was 91 ± 2. The mean social functioning score was 92 ± 3.0. The mean school functioning score was 95.7 in males and 98.5 in females. Associated anomalies and reoperation significantly predicted poor QoL. Increasing years after completion of surgery was significantl associated with good QoL scores. Conclusion: The overall QoL of the participants was good. Associated anomalies and reoperation were associated with poor QoL, while years after completion of definitive surgery was associated with good QoL. There is need for increased awareness and utilization of QoL assessments as an outcome measure after definitive surgery for ARM.
Keywords: Anorectal malformations; Quality of life; Posterior sagittal anorectoplasty; Pediatric surgery